INHIBITION OF ELECTRON-TRANSFER REACTIONS AT THE MERCURY ACETONITRILE INTERFACE BY ADSORBED LITHIUM IONS - Compton, R; Northing, R; Quarrell, R (1989)
The electro-reductions of fluoranthene, crystal violet, anthraquinone, 2,3-dichloro-5,6-dicyano-1,4-benzoquinone, p-dinitrobenzene, pyromtellitic anhydride, tetrachloro-1,4-benzoquinone and tetracyanoethene, in acetonitrile solution, at mercury electodes are all shown to be inhibited by low (ca.) 10-3 mol dm-3 levels of Li+ ions. A.c. impedance data show the formation of a thick (ca. 30 Å) layer of the solvated ions at the mercury/acetonitrile interface and the resulting increased distance for electron tunnelling between the electrode and an electroactive species in solution is suggested to be a possible cause of the inhibition.